Biodegradable wood-based heterostructure composite film as well as preparation method and application thereof

The biodegradable wood-based heterostructure composite membrane was prepared by heterostructure hybrid connection method, which solved the problems of non-renewable and environmental pollution of existing water treatment membrane materials, and achieved high-performance and environmentally friendly water treatment effects.

CN119158421AActive Publication Date: 2024-12-20NORTHEAST FORESTRY UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411284673.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-13
Publication Date
2024-12-20
Estimated Expiration
2044-09-13

AI Technical Summary

Technical Problem

The existing water treatment separation membrane is mainly made of non-renewable petroleum-based polymers, which leads to the pollution of the environment by obtaining membrane materials, traditional membrane preparation process and waste membrane disposal. The selection of cellulose is relatively limited, making it difficult to achieve high performance and Environmentally friendly wood-based separation membrane.

Method used

The biodegradable wood-based heterostructure composite membrane was prepared by the strategy of hybrid connection of heterostructures. The combination of oxidized wood film, covalent organic frame (COF) and polymer optimization layer was used to form a wood-based heterostructure with high performance. Composite film.

Benefits of technology

It achieves high dye removal rate, low salt removal rate and high permeability, has good operating stability, antifouling properties and soil degradability, and provides an environmentally friendly wood-based heterostructure composite membrane for water purification. application.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119158421A_ABST
    Figure CN119158421A_ABST
Patent Text Reader

Abstract

The invention discloses a biodegradable wood-based heterostructure composite membrane as well as a preparation method and application thereof, and belongs to the technical field of development and application of forest-derived materials and wastewater purification and separation. The biodegradable wood-based heterostructure composite film is prepared by adopting a heterostructure mixed connection strategy, and the prepared composite film consists of an original wood film, a COF (Covalent Organic Framework) active layer and a polymer optimization layer, and can be applied to separation of dyes, inorganic salts and mixtures of the dyes and the inorganic salts; the dye is one or more of methylene blue, methyl orange, crystal violet, Congo red, methyl blue and tiger red, and the inorganic salt is one or more of sodium chloride, sodium sulfate, magnesium chloride and magnesium sulfate. The composite membrane has certain operation stability, good antifouling property and soil degradability. In general, the present invention enables the design and manufacture of nanofiltration membranes to be extracted from and used in nature, thereby achieving efficient and sustainable water purification applications.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of development and application of forest-derived materials and wastewater purification and separation technology, and specifically relates to a biodegradable wood-based heterogeneous structure composite membrane, a preparation method and application thereof. Background Art

[0002] With the rapid development of industrialization and urbanization, the amount of wastewater discharge has been increasing, posing a serious threat to the environment and human health. Printing and dyeing wastewater is one of the main harmful industrial wastewaters, mainly derived from the production of dyes and dye intermediates. Among the many wastewater treatment technologies, advanced nanofiltration membranes are indispensable in many fields such as seawater desalination, wastewater treatment, dye recovery, and drug desalination. It is undeniable that membrane materials, as the key to membrane structure and membrane separation performance, are closely related to membrane performance and promote each other. Applying suitable materials and developing effective strategies are one of the ways to obtain high-performance membranes.

[0003] At present, water treatment separation membranes dominate the global separation membrane market. With the deepening of the concept of sustainable development, environmental protection issues, resource utilization and new energy development have put forward higher requirements for separation technology. High-performance membrane materials are also listed as one of the new chemical materials products encouraged to develop in my country, which can make important contributions to the implementation of the sustainable development strategy. However, since the vast majority of water treatment separation membranes are currently made of non-renewable petroleum-based polymers extracted from fossil resources, the acquisition of membrane materials, traditional membrane preparation processes and disposal of waste membranes will generate a large amount of difficult-to-handle waste, thereby causing certain pollution to the ecological environment. In view of this, the green, low-carbon and sustainable development of membrane separation technology has received more and more attention.

[0004] In order to achieve environmental protection of membrane separation technology, researchers usually choose greener chemical reagents and preparation methods or choose to develop more environmentally friendly membrane substrate materials. The survey found that using bio-based materials to replace non-renewable petroleum-based materials has become the main means for researchers to develop environmentally friendly materials. Cellulose has become a strong candidate to replace petroleum-based materials due to its abundant reserves in nature, versatility, and green sustainability. However, the current choice of cellulose is relatively limited, and there is also the problem of choosing cheap and green solvents to achieve ultra-fast cellulose dissolution and the construction of orderly and robust cellulose membranes. In comparison, directly designing natural wood rich in cellulose may bring a series of opportunities. At present, there are few reports on the invention of wood-based separation membranes.

[0005] In summary, the invention of the preparation method of the naturally degradable wood-based heterostructure composite membrane and the exploration of separation performance are of great significance for the future research and development of systematic construction of wood-based nanofiltration membranes. The selection of suitable membrane materials, optimization of operating conditions, and utilization of energy recovery and system integration can further improve the energy-saving performance of membrane separation technology. It can be foreseen that the structural design and innovative selection of membrane substrates of the present invention will provide a simple and effective method for the next generation of development of wood-based heterostructure composite membranes with good separation performance and environmental friendliness, which has great development potential and broad application prospects. Summary of the invention

[0006] The purpose of the present invention is to provide a biodegradable wood-based heterogeneous structure composite membrane, a preparation method and its application, so as to solve the above-mentioned problems existing in the prior art. The present invention adopts a strategy of heterogeneous structure hybrid connection to prepare a biodegradable wood-based heterogeneous structure composite membrane, and the prepared composite membrane is composed of an original wood membrane, a COF (covalent organic framework) active layer and a polymer optimization layer. The biodegradable wood-based heterogeneous structure composite membrane prepared by the present invention has important application value in the separation of inorganic salts and dyes.

[0007] The method for preparing a biodegradable wood-based heterogeneous structure composite film of the present invention comprises the following steps:

[0008] 1) After planing the log, a long strip of wood with a certain thickness is obtained, and then the long strip of wood is evenly cut into the same size, and then the impurities on the surface are cleaned with deionized water, and the original wooden mold is obtained after natural drying for standby use;

[0009] 2) preparing a sodium periodate aqueous solution of a certain volume and a certain molar concentration as an oxidizing solution, and adding glacial acetic acid to adjust the oxidizing solution to acidity after ultrasonic dissolution; immersing the original wood film obtained in step 1) therein, and performing an oxidation reaction at room temperature and in the dark, and obtaining an oxidation layer with a thickness of 0.005 to 0.02 μm on the surface of the original wood film after the reaction, that is, obtaining an oxidized wood film; after the reaction, taking out the original wood film and rinsing it with distilled water for 3 to 5 times; immersing the rinsed original wood film in a 1.4-dioxane solution containing p-phenylenediamine, and the solution quickly changes from colorless to reddish brown, and taking it out after reacting at room temperature for a period of time, and obtaining a Pa layer with a thickness of 0.01 to 0.03 μm on the surface of the oxidized wood film after drying, that is, obtaining a Pa-wood film, which is black;

[0010] 3) ultrasonically dissolving the aldehyde compound and the amine compound in dimethyl sulfoxide to cause a Schiff base reaction, ultrasonically dissolving to obtain a uniform solution, and then standing at room temperature to obtain an iCOF colloidal solution. As the reaction proceeds, it is observed that the yellow color of the colloidal solution gradually deepens; then immersing the original wood film obtained in step 2) into the iCOF colloidal solution, and after reaction at room temperature, an iCOF layer with a thickness of 0.01 to 0.03 μm is obtained on the surface of the Pa-wood film, that is, an iCOF-wood film is obtained;

[0011] 4) dissolving the polymer in dimethyl sulfoxide, stirring the reaction in a water bath to obtain a uniform light yellow polymer solution; absorbing the polymer solution and uniformly coating the surface of the iCOF-wood film obtained in step 3), placing it at room temperature and then drying it in an oven to form a solid polymer layer with a thickness of 0.02 to 0.05 μm on the surface of the iCOF-wood film, thereby obtaining the biodegradable wood-based heterogeneous structure composite membrane (SPEEK-Na@iCOF-wood membrane).

[0012] Preferably, the log in step 1) is pine, and the size of the original wood film is 20-30 mm (length) × 20-30 mm (width) × 0.2-0.6 mm (thickness);

[0013] Preferably, in step 2), 80 to 120 mL of a sodium periodate aqueous solution with a molar concentration of 0.05 to 0.2 mol / L is prepared as an oxidizing solution, and the ultrasonic dissolution time is 2 to 5 minutes; the mass of the original wood film added is 1.5 to 5 g;

[0014] Preferably, in step 2), glacial acetic acid is used to adjust the pH of the oxidation solution to 2-5, the oxidation reaction temperature is 20-30° C., and the oxidation reaction time is 20-30 h;

[0015] Preferably, in step 2), the molar concentration of p-phenylenediamine in the 1,4-dioxane solution is 0.005-0.02 mol / L, the reaction temperature of the oxidized wood film therein is 20-30° C., and the reaction time is 20-30 h;

[0016] Preferably, in step 3), the molar ratio of the amine compound to the aldehyde compound is 0.2-1:0.75, the amine compound is triaminoguanidine hydrochloride, and the aldehyde compound is terephthalaldehyde;

[0017] Preferably, in step 4), the polymer is SPEEK-Na, the concentration of the polymer solution is 20-65 mg / mL, the dissolution temperature is 60-80°C, and the dissolution time is 3-6 hours; the water bath temperature is 50-70°C, the water bath stirring time is 3-6 hours, the placement time at room temperature is 1-3 hours, and the drying temperature is 50-80°C.

[0018] The biodegradable wood-based heterogeneous structure composite membrane described in the present invention is prepared by the above method.

[0019] The biodegradable wood-based heterogeneous structure composite membrane prepared by the invention can be used in separating dyes, and the dye is one or more of methylene blue, methyl orange, crystal violet, Congo red, methyl blue and bengal.

[0020] The biodegradable wood-based heterogeneous structure composite membrane prepared by the present invention can be used in separating inorganic salts, and the inorganic salt is one or more of sodium chloride, sodium sulfate, magnesium chloride and magnesium sulfate.

[0021] The biodegradable wood-based heterogeneous structure composite membrane prepared by the present invention can be used in separating a mixture of an inorganic salt and a dye, wherein the inorganic salt is one or more of sodium chloride, sodium sulfate, magnesium chloride, and magnesium sulfate, and the dye is one or more of methylene blue, methyl orange, crystal violet, Congo red, methyl blue, and bengal.

[0022] The principle of the present invention is to prepare a biodegradable wood-based heterogeneous structure composite membrane by sequentially growing iCOF and SPEEK-Na on a wood substrate by an in-situ symbiotic method. First, amine compounds and aldehyde compounds are completely dissolved in a dimethyl sulfoxide solvent and then uniformly mixed to generate a Schiff base reaction, and a uniformly dispersed iCOF colloidal liquid is obtained after standing at room temperature, and then the iCOF colloidal liquid is assembled on the treated wood film by a simple in-situ growth strategy, and the synthesized cationic imine covalent organic framework is covered on the surface of the pretreated wood film, and the cationic covalent organic framework and the negatively charged wood film support layer are closely combined by electrostatic interaction to modify the wood film support layer, thereby achieving the effect of changing its surface physicochemical properties, and avoiding the problem of decreased membrane performance caused by unstable membrane layer and separation from the support layer in practical applications. When negatively charged SPEEK-Na is introduced, SPEEK-Na can be closely combined with the wood-based membrane through electrostatic interaction, hydrogen bonding and π-π interaction with iCOF, thereby generating a stable mixed heterogeneous structure.

[0023] Compared with the prior art, the present invention has the following advantages and technical effects:

[0024] The present invention aims to invent an environmentally friendly biodegradable membrane with a certain salt-dye separation ability to replace the non-degradable petroleum-based material membrane. The biodegradable wood-based heterogeneous structure composite membrane prepared by this method has a certain application value in salt and dye separation.

[0025] The wood-based heterogeneous structure composite membrane prepared by the present invention has high dye removal rate (>97%), low salt removal rate (<10%) and high permeation flux (172.34L m-2 h -1 bar -1 ), which is superior to many reported dye / salt separation membrane materials. In addition, the composite membrane also has certain operational stability, good antifouling and soil degradability. Overall, this work enables the design and manufacture of nanofiltration membranes to be extracted from and used in nature, thereby achieving efficient and sustainable water purification applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.

[0027] Figure 1 (a) is the ATR-FTIR spectrum of SPEEK-Na@iCOF-wood membrane and the products of each step in Example 1, Figure 1 (b) is the liquid ATR-FTIR spectrum of the colloidal solution in Example 1, Figure 1 (c) is the particle size curve in the colloidal solution;

[0028] Figure 2 (ac) are cross-sectional SEM images of the original wood film, iCOF-wood film, and SPEEK-Na@iCOF-wood film in Example 1, respectively. Figure 2 (df) is the surface scanning electron microscopy image of the original wood film, iCOF-wood film, and SPEEK-Na@iCOF-wood film in Example 1. Figure 2 (gi) is the atomic force microscopy image of the original wood film, iCOF-wood film, and SPEEK-Na@iCOF-wood film in Example 1;

[0029] Figure 3 (a) is a bar graph showing the separation performance of different dyes using the iCOF-wood membrane and SPEEK-Na@iCOF-wood membrane in Example 1. Figure 3 (b) is a bar graph showing the separation performance of bengal red dye using original wood membrane, iCOF-wood membrane, and SPEEK-Na@iCOF-wood membrane. Figure 3 (c) is a bar chart showing the separation performance of four inorganic salts, NaCl, Na2SO4, MgCl2, and MgSO4, using SPEEK-Na@iCOF-wood membrane. Figure 3 (d) is a bar graph showing the separation performance of a mixture of four inorganic salts, NaCl, Na2SO4, MgCl2, and MgSO4, and bengal dye using SPEEK-Na@iCOF-wood membrane. Figure 3(e) is a bar graph showing the separation performance of SPEEK-Na@iCOF-wood membrane for different concentrations of bengal red dye and sodium chloride salt;

[0030] Figure 4 (a) is the anti-pollution performance curve of the iCOF-wood membrane and SPEEK-Na@iCOF-wood membrane in Example 1, Figure 4 (b) is a bar chart showing the anti-pollution performance indexes of iCOF-wood membrane and SPEEK-Na@iCOF-wood membrane. Figure 4 (c) is a bar graph showing the separation and recycling capacity of SPEEK-Na@iCOF-wood membrane for bengal dye. Figure 4 (d) is a long-term stability test curve of tiger red dye using SPEEK-Na@iCOF-wood film;

[0031] Figure 5 (ab) are the actual photos of five membrane materials (NF1, NF6, original wood membrane, iCOF-wood membrane and SPEEK-Na@iCOF-wood membrane) before and after degradation of activated sludge and normal soil. Figure 5 (cd) are the weight loss curves of five membrane materials (NF1, NF6, original wood membrane, iCOF-wood membrane and SPEEK-Na@iCOF-wood membrane) buried in activated sludge and normal soil for 90 days. Figure 5 (e) Actual photos of the degradation of five membrane materials (NF1, NF6, original wood membrane, iCOF-wood membrane and SPEEK-Na@iCOF-wood membrane) buried in activated sludge and normal soil for 90 days.

[0032] Table 1: Parameter data of composition differences between activated sludge and normal soil

[0033] DETAILED DESCRIPTION

[0034] Exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0035] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0036] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0037] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present application description and examples are exemplary only.

[0038] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0039] It should be noted that, unless otherwise specified, % in Examples and Comparative Examples is based on mass.

[0040] The raw materials required in the embodiments of the present invention are all purchased from commercial sources.

[0041] The cross-flow filtration devices used in the separation tests in the embodiments of the present invention all used small membrane flat plate test machines (TYLG-17) purchased from Shandong Bona Group.

[0042] Example 1: A method for preparing a biodegradable wood-based heterogeneous composite membrane

[0043] 1) After planing the pine log, a long strip of wood with a thickness of 440 μm is obtained, and then the long strip of wood is evenly cut into original wood films of 25 mm (length) × 25 mm (width); surface impurities are cleaned with deionized water, and the film is naturally dried for standby use;

[0044] 2) Prepare 100 mL of sodium periodate aqueous solution with a molar concentration of 0.1 mol / L as an oxidizing solution, ultrasonically dissolve for 2 min, then add glacial acetic acid to make the pH of the oxidizing solution = 3; weigh 2.00 g (about 18 pieces) of the original wood film obtained in step 1) and immerse it in it, oxidize it under 25°C and dark conditions for 24 hours, and obtain an oxidation layer (oxidized wood film) with a thickness of 0.01 μm on the surface of the original wood film; after the reaction is completed, take out the oxidized wood film and rinse it with distilled water for 3 times; then immerse all of the above 2.00 g of oxidized wood film in a volume of 50 mL of 1,4-dioxane solution containing 0.01 mmol p-phenylenediamine (Pa), and the solution quickly changes from colorless to reddish brown. After reacting at room temperature for 24 hours, take it out, and obtain a Pa layer (Pa-wood film) with a thickness of 0.015 μm on the surface of the oxidized wood film, and put it into ionized water for standby use; the reaction formula is as follows:

[0045]

[0046] 3) 0.75 mmol of terephthalaldehyde and 0.5 mmol of triaminoguanidine hydrochloride were dissolved in 30 mL of dimethyl sulfoxide to react with a Schiff base. The solution was dissolved by ultrasonic for 20 min to obtain a uniform solution. As the reaction proceeded, the yellow color of the colloidal solution gradually deepened. The uniform solution was allowed to stand at room temperature for 24 h to obtain an iCOF colloidal solution. The reaction formula is as follows:

[0047]

[0048] Then, the Pa-wood film obtained in step 2) is immersed in a COF colloid solution and reacted at room temperature for 24 hours to obtain an iCOF layer (iCOF-wood film) with a thickness of 0.015 μm on the surface of the Pa-wood film;

[0049] 4) dissolving 50 mg / mL of SPEEK-Na solid in dimethyl sulfoxide, stirring in a 60°C water bath for 4 hours to obtain a uniform light yellow liquid; taking a certain amount of SPEEK-Na solution, uniformly coating it on the surface of the iCOF-wood film obtained in step 3), leaving it at room temperature for 2 hours, and then placing it in an oven and drying it at 60°C until a solid polymer layer is formed on the surface of the iCOF-wood film with a thickness of about 0.03 μm; thereby obtaining the biodegradable wood-based heterogeneous structure composite membrane, denoted as SPEEK-Na@iCOF-wood membrane, with a total thickness of 440.07 μm.

[0050] Figure 1 (a) is the infrared spectra (ATR-FTIR) of logs, oxidized wood films, Pa-wood films, iCOF-wood films and SPEEK-Na@iCOF-wood films in Example 1; ATR-FTIR shows that after wood oxidation, the -1The C=O stretching vibration peak at 1640 cm-1 was observed, confirming that sodium periodate successfully oxidized the -OH groups in the wood cellulose molecules to form aldehyde groups. -1 The characteristic peak of C=N appeared at 1024 cm-1, indicating that the aldehyde group generated on the wood matrix can react with the p-phenylenediamine monomer and the amino group of iCOF to form an imine bond, which indicates that the reaction between the aldehyde group and the amine group occurred successfully. When SPEEK-Na was introduced into the iCOF-wood film, the spectrum showed that the peak at 1024 cm-1 was -1 and 1080cm -1 The characteristic absorption peaks at correspond to the symmetric and asymmetric stretching vibrations of the sulfonic acid group (O=S=O), which proves the successful growth of SPEEK-Na; Figure 1 (b) ATR-FTIR spectrum at 1640 cm -1 A new characteristic peak appeared at , which corresponded to the C=N characteristic peak after 24h of mixed reaction of triaminoguanidine hydrochloride and terephthalaldehyde monomer, and an obvious Tyndall effect was observed, which confirmed the successful formation of iCOF colloidal solution. Figure 1 (c) is the specific particle size value of the colloidal solution before and after the reaction in Example 1. The average particle size increases from 55 nm to 78 nm, confirming the growth behavior of iCOF within 24 h.

[0051] Figure 2 (ac) are cross-sectional SEM images of the original wood film, iCOF-wood film, and SPEEK-Na@iCOF-wood film prepared in Example 1. Figure 2 (df) is the surface scanning electron microscope image, Figure 2 (gi) is an atomic force microscope image, from Figure 2 (ac) It can be seen that the cross-sectional morphology of the original wood film presents a clear layered structure, and the iCOF layer mainly grows on the wood surface. When SPEEK-Na is added, a dense coating appears on the surface of the iCOF-wood film. Figure 2 (df) It can be seen that compared with the untreated original wood film, the surface of the iCOF wood presents a rough sponge-like structure, which can be observed under a high-power microscope ( Figure 2 (e) Inset), it can be observed that solid particles are accumulated on the surface of the iCOF-wood film. After the introduction of SPEEK-Na, a dense coating was observed on the surface of the iCOF-wood film. SPEEK-Na evenly covered the surface of the iCOF-wood film, making its surface smoother. In addition, the high-magnification SEM image ( Figure 2 The inset in (f) shows that the SPEEK-Na chains formed nodule-like structures on the surface of the iCOF-wood film. Atomic force microscopy image ( Figure 2(gi)) reflects that the membrane surface roughness is 23.4nm, 68.9nm and 2.15nm, respectively, showing a state of reduced roughness, which is beneficial to the increase of permeation flux.

[0052] Example 2: Separation performance test

[0053] The separation performance of the biodegradable wood-based heterostructure composite membrane prepared in Example 1 was measured by a circulating cross-flow filtration method using a 5 mg / L rose bengal aqueous solution, and the separation performance of the membrane was measured at a pressure of 0.5 bar using 5 mg / L (aqueous solution) dyes (Rose Bengal, negatively charged, 1072.8 Da), methyl blue (Methyl Blue, negatively charged, 799.8 Da), Congo Red (Congo Red, 2 negative charges, 696.66 Da), Crystal Violet (Crystal Violet, positively charged, 407.99 Da), Methylene Blue (Methylene Blue, positively charged, 319.9 Da) and Methyl Orange (Methyl Orange, negatively charged, 327.3 Da)) or 1 g / L inorganic salt solution (aqueous solution) (sodium chloride, magnesium chloride, sodium sulfate and magnesium sulfate) as the feed solution.

[0054] like Figure 3 As shown in (a), the iCOF-wood membrane has a decreasing retention rate and increasing permeation flux for dye separation as the molecular weight of the dye decreases. For crystal violet, the retention rate of the dye shows an opposite trend, which is due to the electrostatic repulsion between the positively charged crystal violet and the positively charged iCOF layer containing triaminoguanidine hydrochloride monomer. Therefore, crystal violet (positively charged) shows a better repulsion effect than Congo red (negatively charged). For the positively charged methylene blue dye, due to its small molecular weight, its repulsion effect is similar to that of Congo red. The retention rate of SPEEK-Na@iCOF-wood membrane for tiger red, methyl blue and Congo red is above 90%. Based on the Donnan effect, it is shown that the introduction of negatively charged polymers makes the wood-based heterostructure membrane have good repulsion performance for negatively charged dyes. However, due to the small molecular weight of methyl orange and its linear molecular formula, it is easy to pass through the wood-based heterostructure membrane, so the repulsion rate is low. Figure 3 (b) More intuitively reflects the retention rate and permeation flux of the original wood membrane, iCOF-wood membrane and SPEEK-Na@iCOF-wood membrane for bengalensis dye. The retention rate of SPEEK-Na@iCOF-wood membrane for bengalensis dye is 97%, and the permeation flux is 220 L h -1 m -2 bar -1 , indicating good separation performance.

[0055] Figure 3(c) reflects the rejection of the membrane to four inorganic salts. The results show that the rejection rates of different inorganic salts are Na2SO4 (8.66%) > MgSO4 (8.41%) > MgCl2 (5.21%) > NaCl (2.86%). Specifically, the higher rejection of sulfate by SPEEK-Na@iCOF-wood membrane compared with chloride salts is due to the negative charge of the membrane repelling high-valent anions. In addition, the divalent anion SO4 2- (0.38nm) than the monovalent anion Cl - The larger hydration radius (0.33 nm) also contributes to this difference in repulsion. In addition, the negatively charged membrane has a stronger stabilizing electrostatic interaction with divalent cations than with monovalent cations, which explains why the rejection of MgSO4 is lower than that of Na2SO4. However, due to the divalent cation Mg 2+ The hydration radius (0.43 nm) is larger than that of the monovalent cation Na + (0.36nm), so the retention rate of MgCl2 is higher than that of NaCl. In summary, the screening of inorganic salts by SPEEK-Na@iCOF-wood membrane is affected by the synergistic effects of Donnan repulsion, electrostatic interaction and steric repulsion. SPEEK-Na@iCOF-wood membrane can effectively promote the transport of various salts.

[0056] Four types of salts (1 g / L, aqueous solution) were mixed with RB dye (10 mg / L, aqueous solution) in equal volumes, and the biodegradable wood-based heterogeneous structure composite membrane prepared in Example 1 was further subjected to salt-dyeing separation test. Figure 3 (d) shows the performance results of SPEEK-Na@iCOF-wood membrane for the removal of RB from solutions containing Na2SO4, MgSO4, NaCl, or MgCl2. It can be observed that SPEEK-Na@iCOF-wood membrane exhibits good removal efficiency of red bengal molecules in solutions containing all four salts, and the rejection rate (retention rate) of red bengal remains above 95%.

[0057] Different concentrations (5, 10, 15, 20 mg / L) of red bengal solution were mixed with 1 g / L NaCl to study the effect of dye concentration on salt separation. Figure 3As can be seen from (e), changing the dye concentration has little effect on salt separation, and the rejection rate of NaCl remains relatively constant. When the concentration of rose bengal solution reaches 20 mg / L, the rejection rate drops to 90%. This may be because under higher concentration conditions, the electronegativity of the rose bengal solution increases, and the negative charges on the surface of the SPEEK-Na@iCOF-wood membrane are not sufficient to repel the aggregated rose bengal molecules with higher electronegativity, resulting in partial penetration of rose bengal molecules and a decrease in the rejection rate. In addition, various factors such as dye hydration, aggregation, steric hindrance effect, concentration polarization, ionic competitive permeation, and electrostatic repulsion may all cause changes in the selectivity of the membrane for dyes and salts. To sum up, the above results indicate that the SPEEK-Na@iCOF-wood membrane has potential application value in dye / salt separation.

[0058] Example 3: Anti-fouling and stability tests

[0059] Using the biodegradable wood-based heterostructure composite membrane prepared in Example 1, a cross-flow filtration device was used to evaluate the anti-fouling and stability of the membrane. Figure 4 (a) is a line graph showing the change in water flux with pure water and bovine serum albumin (BSA) alternately used as the feed solution; Figure 4 (b) is a bar graph showing the flux recovery rate (PRR), reversible fouling rate (Rr), irreversible fouling rate (Rir), and total fouling rate (Rt) of the membrane calculated after the test. In Figure 4 (b), the pattern in front of the character "iCOF-wood membrane" represents 240 min, and the pattern behind represents 420 min; the pattern in front of the character "SPEEK-Na@iCOF-wood membrane" represents 240 min, and the pattern behind represents 420 min.

[0060] The calculation formulas are as follows:

[0061] PRR% = F w,2 / F w,1 × 100% (1)

[0062] Rr% = (F w,2 - F P ) / F w,1 × 100% (2)

[0063] Rir% = (F w,1 - F w,2 ) / F w,1 × 100% (3)

[0064] Rt% = Rr% + Rir% = (F w,1 - F p ) / Fw,1 × 100% (4)

[0065] In the formula, F w,1 is the water flux when pure water is used as feed after pre-pressing, F p is the water flux when the BSA aqueous solution replaces pure water as feed, F w,2 It is the water flux when the membrane, which has been cleaned with water and contaminated with bovine serum albumin, is fed with pure water again.

[0066] Figure 4 (a) When BSA feed was passed through the membrane, the pure water flux of all membranes decreased. After 60 min of pure water permeation with BSA as feed solution, the permeability of iCOF-wood membrane decreased significantly from 290.81 Lh -1 m -2 bar -1 Down to 247.77Lh -1 m -2 bar -1 Similarly, the permeability of SPEEK-Na@iCOF-wooden mold also decreased significantly, from 247.43 L h - 1 m -2 bar -1 Down to 178.54L h -1 m -2 bar -1 The main reasons for the decrease in permeability are the accumulation of BSA on the membrane surface to form a fouling layer and the occurrence of concentration polarization. In order to accurately compare the anti-fouling ability of iCOF-wood membrane and SPEEK-Na@iCOF-wood membrane, we further calculated the relevant indicators. Figure 4 (b) After 210 min of filtration (the first cycle), the water flux recovery rate of the SPEEK-Na@iCOF-wood membrane was 96.41%, the reversible scaling rate was 27.0%, the irreversible scaling rate was 3.59%, and the total scaling rate was 30.59%. The flux recovery rate (96.41%) was better than that of the iCOF-wood membrane (92.93%). In addition, after the second pollution cycle, the water flux recovery rate of the SPEEK-Na@iCOF-wood membrane was still in a good state, indicating that the biodegradable wood-based heterogeneous structure composite membrane prepared in Example 1 has good anti-pollution properties.

[0067] In addition to anti-fouling performance, stability is also an important factor affecting the service life of composite membranes. Figure 4 (c) shows that after 5 cycles of testing, the retention rate of SPEEK-Na@iCOF-wood membrane for bengalensis solution remains at about 90%. In addition, Figure 4(d) It can be seen that after 500 minutes of continuous filtration, the permeation flux of SPEEK-Na@iCOF-wooden model is basically stable, and the retention rate of bengalen red solution is about 90%. The above can illustrate the good stability of the membrane.

[0068] Example 4: Biodegradation Experiment

[0069] Biodegradation experiments were conducted using the biodegradable wood-based heterostructure composite membrane prepared in Example 1 and a commercial nanofiltration membrane.

[0070] The specific operation is as follows: Cut the membrane into a size of 25mm×25mm×0.44mm and store it at 60℃ for 12h. Then measure the initial dry weight m1. Prepare two soil environments: activated sludge and normal soil (see Table 1 for specific parameter differences). After stabilization in the greenhouse for 24h, measure and record the relevant parameters of the two soil environments. During the entire test, the temperature and humidity of the soil were kept at a relatively stable level. Each group of three parallels, bury the cut membrane in the soil at a depth of 10 cm. According to the experimental phenomenon, choose the appropriate time to record the degradation. Before quality inspection, carefully collect the membrane samples from the soil and clean the decomposed samples with a soft brush. Rinse the soil attached to the surface of the sample with distilled water, dry it at 60℃ for 12h, and weigh it as m2. Record the soil biodegradation rate according to the following formula (5):

[0071]

[0072] After each sampling, the soil was gently stirred to maintain a certain aerobic condition. Two commercially available nanofiltration membranes, NF-1 (polyamide material) and NF-6 (polyethersulfone material), were used as control inspection groups.

[0073] Figure 5 (ab) Digital photos intuitively show the degradation of all membranes after being buried in activated sludge / normal soil for about 90 days (from left to right in the picture are NF1, NF6, original wood membrane, iCOF-wood membrane and SPEEK-Na@iCOF-wood membrane). It can be seen that over time, due to the degradability of cellulose and hemicellulose in wood, the original wood mold, iCOF-wood membrane and SPEEK-Na@iCOF-wood membrane gradually lost their original luster and showed cracking and fragmentation, which shows that wood shows a certain degradation ability in both soil environments. Figure 5 (cd) Detailed data on film weight loss and detailed digital photos within 90 days Figure 5(e) It can further support the degradation ability of wood-based membranes. After about 90 days of continuous changes in ambient temperature and relative humidity, it was observed that SPEEK-Na@iCOF-wood membranes degraded by about 80% in activated sludge and about 60% in normal soil. This degradation phenomenon is mainly due to the stronger hydrophilicity and porous structure of SPEEK-Na@iCOF-wood membranes, which are more conducive to the growth of microorganisms and accelerate the degradation process. The difference in organic matter content in the two soil environments is the main factor leading to the difference in soil degradation. Activated sludge showed a higher organic matter content, resulting in more obvious degradation of SPEEK-Na@iCOF-wood membranes than normal soil in the same period. Under the same conditions, since the two commercial membranes are mainly composed of -CC and -CH covalent bonds that are not easily hydrolyzed, coupled with the large spatial barrier formed by the macromolecular segments, they showed lower soil degradation ability. Therefore, the SPEEK-Na@iCOF-wood membrane prepared by the present invention is a sustainable green material that can be buried in the soil for biodegradation and returned to nature without causing white pollution.

[0074] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. A method for preparing a biodegradable wood-based heterogeneous structure composite film, the steps of which are as follows: 1) After planing the log, a long strip of wood with a certain thickness is obtained, and then the long strip of wood is evenly cut into the same size, and then the impurities on the surface are cleaned with deionized water, and the original wooden mold is obtained after natural drying; 2) preparing a sodium periodate aqueous solution of a certain volume and molar concentration as an oxidizing solution, dissolving it by ultrasonication, adding glacial acetic acid to adjust the oxidizing solution to acidity; immersing the original wood film obtained in step 1) in, The oxidation reaction is carried out at room temperature and in the dark, and after the reaction, an oxide layer with a thickness of 0.005 to 0.02 μm is obtained on the surface of the original wood film, that is, an oxidized wood film is obtained; after the reaction is completed, the original wood film is taken out and rinsed with distilled water for 3 to 5 times; the rinsed original wood film is immersed in a 1.4-dioxane solution containing p-phenylenediamine, and the solution quickly changes from colorless to reddish brown, and after reacting for a period of time at room temperature, the original wood film is taken out, and after drying, a Pa layer with a thickness of 0.01 to 0.03 μm is obtained on the surface of the oxidized wood film, that is, a Pa-wood film is obtained, which is black; 3) ultrasonically dissolving the aldehyde compound and the amine compound in dimethyl sulfoxide to cause a Schiff base reaction, ultrasonically dissolving to obtain a uniform solution, and then standing at room temperature to obtain an iCOF colloidal solution. As the reaction proceeds, it is observed that the yellow color of the colloidal solution gradually deepens; then immersing the original wood film obtained in step 2) into the iCOF colloidal solution, and after reaction at room temperature, an iCOF layer with a thickness of 0.01 to 0.03 μm is obtained on the surface of the Pa-wood film, that is, an iCOF-wood film is obtained; 4) dissolving the polymer in dimethyl sulfoxide, stirring the reaction in a water bath to obtain a uniform light yellow polymer solution; absorbing the polymer solution and uniformly coating the surface of the iCOF-wood film obtained in step 3), leaving it at room temperature and then drying it in an oven to form a solid polymer layer with a thickness of 0.02 to 0.05 μm on the surface of the iCOF-wood film, thereby obtaining the biodegradable wood-based heterogeneous structure composite membrane.

2. A method for preparing a biodegradable wood-based heterogeneous composite membrane according to claim 1, Features: The log in step 1) is pine, and the size of the original wood film is (20-30) mm×(20-30) mm×(0.2-0.6) mm.

3. A method for preparing a biodegradable wood-based heterogeneous structure composite membrane according to claim 1, Features: In step 2), 80 to 120 mL of a sodium periodate aqueous solution with a molar concentration of 0.05 to 0.2 mol / L is prepared as an oxidizing solution, and the ultrasonic dissolution time is 2 to 5 minutes; the mass of the original wood film added is 1.5 to 5 g; the pH of the oxidizing solution is adjusted to 2 to 5 with glacial acetic acid, the oxidation reaction temperature is 20 to 30° C., and the oxidation reaction time is 20 to 30 hours.

4. The method for preparing a biodegradable wood-based heterogeneous composite membrane according to claim 1, Features: In step 2), the molar concentration of p-phenylenediamine in the 1,4-dioxane solution is 0.005-0.02 mol / L, the reaction temperature of the oxidized wood film therein is 20-30° C., and the reaction time is 20-30 h.

5. The method for preparing a biodegradable wood-based heterogeneous structure composite film according to claim 1, Features: In step 3), the molar ratio of the amine compound to the aldehyde compound is 0.2-1:0.75, the amine compound is triaminoguanidine hydrochloride, and the aldehyde compound is terephthalaldehyde.

6. A method for preparing a biodegradable wood-based heterogeneous composite membrane according to claim 1, Features: In step 4), the polymer is SPEEK-Na, the concentration of the polymer solution is 20-65 mg / mL, the dissolution temperature is 60-80°C, and the dissolution time is 3-6 hours; the water bath temperature is 50-70°C, the water bath stirring time is 3-6 hours, the standing time at room temperature is 1-3 hours, and the drying temperature is 50-80°C.

7. A biodegradable wood-based heterogeneous structure composite membrane, Features: The invention is prepared by the preparation method according to any one of claims 1 to 6.

8. Use of a biodegradable wood-based heterogeneous structure composite membrane as claimed in claim 7 in separating dyes, Features: The dye is one or more of methylene blue, methyl orange, crystal violet, Congo red, methyl blue and red bengal.

9. Use of a biodegradable wood-based heterostructure composite membrane as claimed in claim 7 in separating inorganic salts, Its characteristics are: The inorganic salt is one or more of sodium chloride, sodium sulfate, magnesium chloride and magnesium sulfate.

10. Use of a biodegradable wood-based heterostructure composite membrane according to claim 7 in separating a mixture of an inorganic salt and a dye, Features: The inorganic salt is one or more of sodium chloride, sodium sulfate, magnesium chloride and magnesium sulfate; the dye is one or more of methylene blue, methyl orange, crystal violet, Congo red, methyl blue and bengal.

Citation Information

Patent Citations

  • PSPEEK / COF composite membrane for reverse electrodialysis technology and preparation method of PSPEEK / COF composite membrane

    CN117085517A

  • Nanofiltration membrane and preparation method thereof

    CN117358066A

  • Simplifying Solid-Phase Microextraction (SPME)-Based Analytical Measurements of Exceedingly Small-Volume Samples by Application of Negligible Depletion

    US20210033602A1